Use of lauricellasÂ´s hipergeometric F (3) D in the solution of triple integral equations - Saxena, R. K.; Shthi, P. L. (Rev. Téc. Fac. Ing. Univ. Zulia)
In this paper the authors have presented the formal solutions of triple integral equations associated with Hankels Keenles. It has been sown by the application of known integral involving products of Bessel function and the known solution of Abels integral equation that the problem reduces to that of solving Fredholms integral equitation to the firs kind which can be easily solvent by numerical method. The results given early by gooks and tranter follow, as special case.